Sharing knowledge about immunisation (SKAI): An exploration of parents' communication needs to inform development of a clinical communication support intervention - Berry, N.; Danchin, M.; Trevena, L.; Witteman, H.; Kinnersley, P.; Snelling, Thomas; Robinson, P.; Leask, J. (Elsevier, 2018)
© 2017 Elsevier Ltd. Introduction: The SKAI (Sharing Knowledge About Immunisation) project aims to develop effective communication tools to support primary health care providers' consultations with parents who may be hesitant about vaccinating their children. Aim: This study explored parents' communication needs using a qualitative design. Methods: Parents of at least one child less than five years old were recruited from two major cities and a regional town known for high prevalence of vaccine objection. Focus groups of parents who held similar vaccination attitudes and intentions were convened to discuss experiences of vaccination consultations and explore their communication needs, including preferences. Draft written communication support tools were used to stimulate discussion and gauge acceptability of the tools. Results: Important differences in communication needs between group types emerged. The least hesitant parent groups reported feeling reassured upon reading resources designed to address commonly observed concerns about vaccination. As hesitancy of the group members increased, so did their accounts of the volume and detail of information they required. Trust appeared to be related to apparent or perceived transparency. More hesitant groups displayed increased sensitivity and resistance to persuasive language forms.